2015
DOI: 10.1111/jop.12348
|View full text |Cite
|
Sign up to set email alerts
|

CD44high/ALDH1high head and neck squamous cell carcinoma cells exhibit mesenchymal characteristics and GSK3β‐dependent cancer stem cell properties

Abstract: Our results show that GSK3β plays a major role in maintenance of stemness of CD44(high) /ALDH1(high) HNSCC cells. Additionally, they indicate a close relationship between CSC and mesenchymal characteristics in HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 46 publications
2
45
0
2
Order By: Relevance
“…Our early study and other groups had reported that Lin28B can promote cell malignancy, 10,35 cancer progression, and inflammation-induced carcinogenesis, 33 BMI-1 with oral carcinogenesis, 13 and ALDH1+ cells show cancer stem cell characteristics. 14,15,17 Considering the above mentioned points, we speculated potential relation of TRAF1 with stem cell subpopulations in oral cancer, which needs to be investigated further by molecular mechanism studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our early study and other groups had reported that Lin28B can promote cell malignancy, 10,35 cancer progression, and inflammation-induced carcinogenesis, 33 BMI-1 with oral carcinogenesis, 13 and ALDH1+ cells show cancer stem cell characteristics. 14,15,17 Considering the above mentioned points, we speculated potential relation of TRAF1 with stem cell subpopulations in oral cancer, which needs to be investigated further by molecular mechanism studies.…”
Section: Discussionmentioning
confidence: 99%
“…33 Stem cell markers, including BMI-1, ALDH1, and Lin28B, are associated with head and neck tumorigenesis. 6,7,17 About 40.9% of oral leukoplakia patients with BMI-1 positivity develop oral cancer. 12 ALDH1-high cancer cells exhibit a high tumor sphere-forming ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cells are present in HNSCC, and overexpress CD44 and aldehyde dehydrogenase (ALDH) proteins, which are currently regarded as HNSCC CSCs' markers [127][128][129]. Moncharmont and colleagues reported that consecutive cell sorting was performed to isolate SQ20B/ CSCs from SQ20B parental population utilizing Side Population (SP).…”
Section: Carbon Ion Irradiation Counteracts Cancer Stem Cells' Migratmentioning
confidence: 99%